2013
DOI: 10.3897/zookeys.319.4219
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study of wing interference patterns (WIPs) in some species of soft scale (Hemiptera, Sternorrhyncha, Coccoidea, Coccidae)

Abstract: The fore wings of scale insect males possess reduced venation compared with other insects and the homologies of remaining veins are controversial. The hind wings are reduced to hamulohalterae. When adult males are prepared using the standard methods adopted to females and nymphs, i.e. using KOH to clear the specimens, the wings become damaged or deformed, an so these structures are not usually described or illustrated in publications. The present study used dry males belonging to seven species of the family Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…Within hemimetabolous Sternorrhyncha, there are a few studies on the course of wing veins (Patch 1909 and Klimaszewki and Wojciechowski ( 1993 ) in all Sternorrhyncha; Martin 2007 in whiteflies; Shcherbakov 2007 in aphids and coccids) and on the structure of the wings of coccids (Koteja 1996 ; Simon 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Within hemimetabolous Sternorrhyncha, there are a few studies on the course of wing veins (Patch 1909 and Klimaszewki and Wojciechowski ( 1993 ) in all Sternorrhyncha; Martin 2007 in whiteflies; Shcherbakov 2007 in aphids and coccids) and on the structure of the wings of coccids (Koteja 1996 ; Simon 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The biological significance of WIPs as originally proposed by Shevtsova et al (9) has so far mainly received attention for their potential as diagnostic species identification traits in taxonomic and systematic studies (12)(13)(14). The possible role of WIPs as signaling traits at the intraspecific level where they might be targets of sexual selection (15)(16)(17) has only been hypothesized and has not been experimentally investigated.…”
mentioning
confidence: 99%
“…The interference pattern caused by the ultra-thin but uneven wing membrane can be visualized against a dark background. WIPs have already proven to be of value in generic and even species-level identifications of several insect groups ( Buffington and Sandler 2011 ; Hansson 2011 ; Shevtsova et al 2011 ; Shevtsova and Hansson 2011 ; Simon 2012 ), and ongoing studies found WIPs to be species-specific and showing no sexual dimorphism in some taxa of Miltogramminae (Zhang et al unpublished). We employed this method for comparisons between both sexes of Sarcophaga (Sarcorohdendorfia) gracilior , and the WIPs show no sexual dimorphism ( Figs 5A , 5C ).…”
Section: Discussionmentioning
confidence: 99%
“…Wing interference patterns (WIPs) were recently introduced as a potential new character system of extremely thin insect wings ( Shevtsova et al 2011 ), and it has at this time proven useful for the separation of species in Hymenoptera , Hemiptera and Diptera ( Buffington and Sandler 2011 ; Hansson 2011 ; Shevtsova and Hansson 2011 , Shevtsova et al 2011 ; Simon 2012 ). It might be suspected to provide a useful tool for correctly associating male and female specimens in some Sarcophagidae , and finds support in ongoing studies (Zhang et al, unpublished), and we therefore provide WIPs for both sexes of Sarcophaga (Sarcorohdendorfia) gracilior .…”
Section: Introductionmentioning
confidence: 99%